BDNF-Mediated Cerebellar Granule Cell Development Is Impaired in Mice Null for CaMKK2 or CaMKIV - Kokubo, Manabu (Society for Neuroscience, 2009)
The Ca(2+)/calmodulin-activated kinases CaMKK2 and CaMKIV are highly expressed in the brain where they play important roles in activating intracellular responses to elevated Ca(2+). To address the biological functions of Ca(2+) signaling via these kinases during brain development, we have examined cerebellar development in mice null for CaMKK2 or CaMKIV. Here, we demonstrate that CaMKK2/CaMKIV-dependent phosphorylation of cAMP response element-binding protein (CREB) correlates with Bdnf transcription, which is required for normal development of cerebellar granule cell neurons. We show in vivo and in vitro that the absence of either CaMKK2 or CaMKIV disrupts the ability of developing cerebellar granule cells in the external granule cell layer to cease proliferation and begin migration to the internal granule cell layer. Furthermore, loss of CaMKK2 or CaMKIV results in decreased CREB phosphorylation (pCREB), Bdnf exon I and IV-containing mRNAs, and brain-derived neurotrophic factor (BDNF) protein in cerebellar granule cell neurons. Reexpression of CaMKK2 or CaMKIV in granule cells that lack CaMKK2 or CaMKIV, respectively, restores pCREB and BDNF to wild-type levels and addition of BDNF rescues granule cell migration in vitro. These results reveal a previously undefined role for a CaMKK2/CaMKIV cascade involved in cerebellar granule cell development and show specifically that Ca(2+)-dependent regulation of BDNF through CaMKK2/CaMKIV is required for this process.